New development: Integrating risk management in management control systems—lessons for public sector managers. Issue 2 (17th February 2019) - Rana, Tarek; Wickramasinghe, Danture; Bracci, Enrico
ABSTRACT: Exploring multiple dimensions of management control systems (MCS), this article proposes a new framework to integrate risk management with strategy, MCS and performance measurement systems (PMS). Considering the public sector as a focal point, the article points to some enterprise risk management (ERM) issues and argues that ERM-enabled MCS has potential to improve PMS and strategic decision-making, leading to a more proactive risk management framework and a culture that promotes performance driven accountability. Consequently, the article calls for further research towards solving the public sector's risk management problems, motivating its managers to adopt best practices, and stimulating suitable policy developments.